Homosexuality in the German Armed Forces - Storkmann, Klaus (De Gruyter, 2025)
Homosexuals were mustered out of military service in the Bundeswehr until 1979, after which homosexuality alone was no longer considered grounds for unsuitability. But for homosexual soldiers, military service was an option, but a career was not – they were generally unable to progress to the rank of officer. Storkmann uses interviews, court files, and internal documents to examine the Bundeswehr’s approach toward homosexual soldiers.